Petite ou grande mort? A sexualidade e o imaginário tecnológico contemporâneo - Tonin, Juliana (2007)
This article examines some implications contained in the new sexual relations established through the machines or with them. Through the discussion over the technological imaginary, as it can be observed in the movies The Lawnmower Man and Artificial Intelligence, and that it seems to presents itself in contemporary practices, this paper conjectures about an eroticism that would be different from that imagined by Bataille. In this new eroticism, underlies a will of the elimination of the other, which is, in the limit, a will of elimination of oneself.